The U.S.-Japan Alliance : past, present, and future - Green, Michael J.; Cronin, Patrick M., editor; Green, Michael J., editor (New York : Council on foreign relations press, 1999)
During the cold war, the U.S.-Japan alliance was at the core of American presence, power, and prestige in the Asia-Pacific Region. When the Cold War ended, many questioned whether the alliance would continue to serve U.S. and Japanese interests. In the late 1990s the United States and Japan answered that question with a formal reaffirmation of the security treaty and the upgrading of bilateral guidelines for defense cooperation. But the alliance has also faced new challenges: domestic opposition to U.S. bases in Okinawa; Chinese criticism of a stronger U.S.-Japan security relationship; and growing international frustration with Japan's economic policies. The alliance remains crucial to both nations' interests, but the management of bilateral security ties has become far more complex.The U.S.-Japan Alliance: Past, Present, and Future explains the inner workings of the U.S.-Japan alliance and recommends new approaches to sustaining this critical bilateral security relationship. The authors are scholars and practitioners who understand where the alliance came from, how it is managed, and the strategic decisions that will have to be made in the future.
Includes bibliographical references and index.
Keywords: United States -- foreign relations -- Japan; United States -- Foreign relations -- Japan -- 20th century